Restructuring the Economic Policy Framework in Brazil: Genuine or Gattopardo change? - Rui Lyrio Modenesi; André de Melo Modenesi; Norberto Montani Martins; Patrick Fontaine (Revue de la Régulation)
We analyzed Brazil’s development since World War II and especially Presidents Lula and Rousseff’s economic policy by integrating historical and political economy approaches using the concept of “development convention”. Two development conventions have been struggling for hegemony: a pro-growth – state led and a pro-stability – free market convention. Until the 1970s, the “developmentalist” convention was dominant. During the 1980s, a stability convention started to ascend; the rise of neoliberalism reinforced the precedence of stability over growth. In 1999, the macroeconomic tripod – inflation targeting; floating exchange rate; and budget surplus targeting – aligned with the New Consensus on Macroeconomics was adopted. As we argued, it locked economy into a trap: low growth; high interest rates; relatively high inflation; and overvalued currency. Since the 2008 Great Crisis, economic policy has been changing in an attempt to foster growth. For orthodox economists, the tripod was marred or dropped and replaced by a Keynesian policy. For Keynesians, it was hold; it is as if the change had just been a Gattopardo change, a “change that keeps things the same”.